2018
DOI: 10.1111/1752-1688.12649
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of River Networks: A GIS Approach and Its Applications

Abstract: Fluvial geomorphology provides the basis for characterizing complex river networks and evaluating biophysical processes within watersheds. Understanding the spatial organization of morphological features, their influencing processes, and resultant geomorphic diversity in stream networks are important for efficient restoration, river health assessment, and improving our knowledge of the resilience of riverine landscapes. River characterization is a means to determine the biophysical character of river networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
(126 reference statements)
0
16
0
Order By: Relevance
“…Accordingly, the physical structure of river networks govern the type, abundance, and arrangement of biological communities found within these networks (cf. Thoms et al, ). This study has shown each FPZ in the Biobío River to have a unique fish community, similarly to specific macroinvertebrate communities and aquatic food web associated with FPZs character (Maasri et al, ; Thoms et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, the physical structure of river networks govern the type, abundance, and arrangement of biological communities found within these networks (cf. Thoms et al, ). This study has shown each FPZ in the Biobío River to have a unique fish community, similarly to specific macroinvertebrate communities and aquatic food web associated with FPZs character (Maasri et al, ; Thoms et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The river networks of the Biobío and Imperial rivers were obtained from the Chilean National Hydrography data set, which provides a 1:50.000‐scale digital representation. The river network of each system was divided into 5‐km reaches following the approach recommended by Thoms et al (). Each reach defined a site and 160 sites were defined in the Biobío River and 187 in Imperial River.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…); Identifying the relative importance of water quality stressors in predicting fish community responses in midwestern streams (Meador and Frey ); Using geographic information system and multivariate statistical methods to characterize river networks for establishing reference conditions and managing threatened and endangered species (Thoms et al. ); Addressing social dimensions of urban flood exposure concerns (Hale et al. ); and How snowpack melt‐out timing correlates with agricultural droughts (Nicholson et al.…”
mentioning
confidence: 99%